CHRONIC INTOXICATION WITH “LAUGHING GAS” (NITROUS OXIDE) AS A CAUSE OF B12 DEFICIENCY MYELOPOLYNEUROPATHY IN YOUNG ADULTS - N. A. Suponeva; D. A. Grishina; L. A. Legostaeva; E. G. Mochalova (Нервно-мышечные болезни)
The problem of using nitrous oxide (“laughing gas”) is now important because young people often prefer this kind of entertainment. Regular short-term inhalation of nitrous oxide increases the risk of developing vitamin B12 deficiency, which is an essential cofactor of important  metabolic processes. This article describes 2 clinical cases of neurological disorders in young adults who had used nitrous oxide. We demonstrate difficulties in the diagnosis, therapeutic tactics and prognosis.